Experimental investigation on thermal characteristics of transcritical CO2 heat pump unit combined with thermal energy storage for residential heating. (25th January 2020) - Wang, Zhihua; Wang, Fenghao; Li, Guichen; Song, Mengjie; Ma, Zhenjun; Ren, Haoshan; Li, Kehua
Highlights: A transcritical CO2 ASHP combined with TES is analyzed using experiment. Effect of primary factors on thermal characteristics of the system are studied. A performance comparison between the system and the heat pump unit was reported. The COPsystem is 17% higher than that of the CO2 ASHP unit without TES (COPunit ). Abstract: A preliminary experimental investigation was carried out to analyze the thermal characteristics of a transcritical CO2 air source heat pump unit with thermal energy storage for residential heating. The primary impact factors such as discharge pressure, ambient temperature, supply/return water temperature were considered. Also, a performance comparison of the combined system with the CO2 air source heat pump unit without thermal energy storage was presented. It was found that the maximum coefficient of performance (COP) of the CO2 air source heat pump unit decreased by 18.8%, and the optimum discharge pressure and the throttle loss increased by 14.7% and 47.5%, respectively, as the water temperature at the inlet of the gas cooler increased from 35 to 45 °C. Additionally, the results also indicated that the COP of the combined system was 17% higher than that of the CO2 air source heat pump unit. However, it was worth noted that the water flow rate should be adjusted according to the supply water temperature in the practical application so as to meet the thermal comfort for user. The experimental results demonstrated that thermal energy storage as a sub-cooler is a promising technology for reducing the throttle loss and improving the COP of the combined system, and is helpful to promote the CO2 air source heat pump application for space heating in cold regions.